Stimulation of angiogenesis through growth factor delivery from synthetic heparinised hydrogels - Chokoza, Cindy (Department of Human Biology, 2017)
Objectives: Vascular diseases are one of the leading causes of death. Due to minimal regenerative capability of the heart, alternative therapies have been sought after with engineered biomaterials being extensively investigated in this area. In this study, enzymatically degradable heparinised polyethylene glycol (PEG-Hep) hydrogels were synthesized and characterised for the binding and controlled release of vascular endothelial growth factor (VEGF) and basic fibroblast growth factor (bFGF), as well as their bioactivity and angiogenic potential in vivo. Methodology: VEGF and bFGF were combined into 4% (m/v) PEG-Hep hydrogels. The binding and release rates of VEGF and BFGF were analysed via an immunosorbent assay. Released growth factor bioactivity was measured using an XTT metabolic assay on human saphenous vein endothelial cells and human dermal fibroblasts. Neovascularisation was quantified in a subcutaneous rat angiogenesis model in which hydrogel growth factor combinations were implanted within porous polyurethane discs and analysed after a 4 week period. A novel hybrid hydrogel able to degrade proteolytically and hydrolytically was further developed, characterised and analysed as above. Results: PEG-Hep hydrogels demonstrated substantial growth factor binding ability (500-600 ng) and allowed sustained release (10-20 ng/day) for up to 28 days. Bioactivity of the growth factors was retained throughout the release period. The degradation rate of the hydrogels could be controlled in vivo by varying the ratio of monomers capable of forming either hydrolytically or proteolytically degradable crosslinks. Qualitative and quantitative analysis demonstrated a pronounced and significant angiogenic response in vivo (p<0.05). Conclusion: Heparinised PEG hydrogels show significant promise as controlled release vehicles for growth factors and warrant further examination in a myocardial infarction model.